PENGARUH SELF-ESTEEM TERHADAP PERILAKU PROKRASTINASI AKADEMIK PADA SISWA DI SMA N 1 MUARO JAMBI - Zidan Alhamdika; Ninil Elfira; Sarman, Freddi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the phenomenon of academic procrastination behavior in students which is characterized by the habit of postponing assignments until the deadline is near. This study aims to determine the level of students' self-esteem, the level of students' academic procrastination, and the influence of self-esteem on academic procrastination behavior in students of SMA Negeri 1 Muaro Jambi. This study uses a quantitative approach with an ex post facto research type. The study population was 708 students of grades X and XI, with a sample of 256. Data collection was carried out through questionnaires, then analyzed using simple linear regression analysis with the help of SPSS. The results showed that the level of students' self-esteem was in the good category, while the level of academic procrastination was in the moderate category. The results of the regression test showed a significance value of 0.000 <0.05 with a regression coefficient of -0.554 and a t-value of -13.787, so that self-esteem had a negative and significant effect on academic procrastination. The coefficient of determination (R²) value of 0.428 indicates that self-esteem contributes 42,8% to academic procrastination. Therefore, it can be concluded that the higher a student's self-esteem, the lower their academic procrastination behavior.